A Review of Perchlorate clo4 ?) Occurrence in Fruits and Vegetables - Escudey-Castro, A; Escudey-Castro, A (Springer International Publishing, 2017)
Since the 1990s, a large number of studies around the world have reported the presence of perchlorate in different types of environmental matrices. In view of their inherent characteristics, such as high solubility, mobility, persistence, and low affinity for the surface of soil, perchlorates are mobilized through the water-soil system and accumulate in edible plant species of high human consumption. However, the ingestion of food products containing perchlorate represents a potential health risk to people due to their adverse effects on thyroid, hormone, and neuronal development, mainly in infants and fetuses. At present, research has been centered on determining sources, fates, and remediation methods and not on its real extension in vegetables under farming conditions. This review presents a comprehensive overview and update of the frequent detection of perchlorate in fruits and vegetables produced and marketed around the world. Additionally, the impact of fertilizer on the potential addition of perchlorate to soil and its mobility in the water-soil-plant system is discussed. This review is organized into the following sections: sources of perchlorate, mobility in the water-soil system, presence in fruits and vegetables in different countries, international regulations, and toxicological studies. Finally, recommendations for future studies concerning perchlorate in fruits and vegetables are presented. © 2017, Springer International Publishing Switzerland.